Biotransformation of methane into methanol by methanotrophs immobilized on coconut coir. (February 2020) - Patel, Sanjay K.S.; Kalia, Vipin Chandra; Joo, Ji Bong; Kang, Yun Chan; Lee, Jung-Kul
Graphical abstract: Highlights: Methanotrophs immobilization on coconut coir as a support is demonstrated. A unique approach to produce methanol in the presence of paraffin oil is established. Higher methanol production (1.6-fold) than by control without paraffin is achieved. Methanol production of 52.9 mmol/L is obtained under repeated batch conditions. Abstract: This study aimed to establish a unique approach for the production of methanol from methane (CH4 ) in the presence of paraffin oil mediated by methanotrophs immobilized on coconut coir (CC). Immobilization of different methanotrophs through covalent method increased the immobilization yield and relative efficiency for methanol production to 48.6% and 96.8%, respectively. In the presence of paraffin oil, methanol production was 1.6-fold higher by Methylocystis bryophila than by control. Compared to free cells, whole cells immobilized on CC showed higher stability for methanol production. Under repeated batch conditions, cumulative methanol production by immobilized cells and free cells, after eight cycles of reuse, was 52.9 and 30.9 mmol/L, respectively. This study effectively demonstrated the beneficial influence of lignocellulosic biowaste CC as support for immobilization of methanotrophs and paraffin oil on bioconversion of CH4 to methanol.